2007
DOI: 10.1111/j.1746-1561.2007.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Children at Risk: The Association Between Perceived Weight Status and Suicidal Thoughts and Attempts in Middle School Youth*

Abstract: Controlling for personal and family characteristics, perceived weight status was significantly associated with suicidal thoughts and actions in middle school boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 25 publications
5
57
3
Order By: Relevance
“…Our analyses confirm previous studies highlighting that there are important associations between perceived body weight and suicidal behavior [3,6] and that perceived weight may be equally, if not more, important for suicidal behaviors than BMI in both cross-sectional [3,5] and longitudinal studies [4]. Our findings complement previous research [3] by documenting that perceived overweight is a statistically significant risk factor for suicide attempts among youth even after controlling for the impact of important confounders such as sadness, alcohol, and illicit drug use.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analyses confirm previous studies highlighting that there are important associations between perceived body weight and suicidal behavior [3,6] and that perceived weight may be equally, if not more, important for suicidal behaviors than BMI in both cross-sectional [3,5] and longitudinal studies [4]. Our findings complement previous research [3] by documenting that perceived overweight is a statistically significant risk factor for suicide attempts among youth even after controlling for the impact of important confounders such as sadness, alcohol, and illicit drug use.…”
Section: Discussionsupporting
confidence: 92%
“…There is an emerging and growing literature examining the influence of perceived weight, weight status, body mass index (BMI), weight control behaviors, and body dissatisfaction [3][4][5][6] that indicate that these may be important risk factors for suicidal behaviors for youth. However, the extent to which perceived and actual overweight, separately or combined, impact risk for suicide attempts in a nationally representative study of youth have not yet been reported, and can have important implications for clinical practice and prevention.…”
mentioning
confidence: 99%
“…Third, suicidal ideation used here was assessed on a five-point scale (strongly agree to strongly disagree). However, ''agree'' and ''strongly agree'' categories were only regarded as ''suicidal ideation'' to conservatively evaluate the relationship between body dissatisfaction and suicidal ideation, although the ''neutral'' may be a positive one if a choice of yes or no for an answer is given as in a number of previous studies [10,11,16,17]. In addition, this study excluded those who did not answer questions about psychological problems at the time of the survey, even though this excluded group might be characterized by a greater likelihood of experiencing suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these factors, a great deal evidence has pointed to a strong relationship between body dissatisfaction and suicidal behavior, including suicidal ideation, in recent years [1,[8][9][10][11][12][13][14][15][16]. However, a causal relationship cannot be drawn between these two issues based on such evidence because of the cross-sectional designs of previous studies.…”
mentioning
confidence: 89%
“…Perceived overweight status has been significantly associated with suicidal thoughts and actions among female middle school children. 8 In a study of weight status and quality of life, children classified as obese reported quality of life levels that were lower than those of healthy children and similar to those with a diagnosis of cancer. 9 Weight problems are persistent.…”
mentioning
confidence: 99%